Art and transformation: experiences and images of the artists of the ¡mira! exhibition (2014)
From a reading of the texts in the dossier ¡Mira! Artes Visuales Contemporáneas de los Pueblos Indígenas (contemporary visual arts of the indigenous peoples), the authors draw attention to the fact that the creative processes narrated by the artists are acts of communication which do not reduce themselves to a cultural translation, since they involve multiple acts of transformation—of the bodies, the techniques, the images and the artists themselves. Their works of art call upon the spectator to become part of such a creative transformability.